Pengaruh Pengetahuan dan Digitalisasi Terhadap Kepatuhan Wajib Pajak Orang Pribadi di PT. Denki Engineering - Azzahra, Salsabila; Krishantoro, Krishantoro (Jurnal Ilmu Administrasi Publik, 2024)
This research aimed to determine the influence of knowledge and digitalization on individual taxpayer compliance at PT. Denki Engineering. The research method used in this research was a quantitative approach. The type of research used in this research was descriptive. The population used in this research was a saturated population who were employees at PT. Denki Engineering. The data collection technique in this research used non-probability sampling with a saturated sample method with a sample of 70. The data analysis used was multiple linear regression analysis using IBM Statistics version 26 software. The research results showed that there was a partial positive and significant influence between the knowledge variable on compliance 0f 46.8%, there was a partial positive and significant influence between the digitalization variable on compliance of 50.1%, there was a partial positive and significant influence between the knowledge variable and digitalization on compliance of 54.8%, the remaining of 45.2% was influence by other variables that were not examined in this research.